2018
DOI: 10.1002/2017ja024781
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Subauroral Polarization Streams on Ionosphere and Thermosphere During the 2015 St. Patrick's Day Storm: Global Ionosphere‐Thermosphere Model Simulations

Abstract: Using the Millstone Hill incoherent scatter radar observations during 2015 St. Patrick's Day storm, subauroral polarization streams (SAPSs) have been specified in the nonhydrostatic Global Ionosphere‐Thermosphere Model simulations. The results reveal that the effect of SAPS on the coupled thermosphere‐ionosphere system includes the following: (1) Sudden frictional heating of SAPS results in acoustic‐gravity waves in the thermosphere. The vertical oscillation is localized, while the meridional disturbance propa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 47 publications
(69 reference statements)
5
42
1
Order By: Relevance
“…TOI shown in the figure was observed off the magnetic pole, more close to the dusk cell when the IMF By became negative. Simulations by Guo et al (2018) have suggested that SAPS related thermospheric heating can possibly induce regional thermospheric and ionospheric disturbances taking the form of TIDs/AGWs as anticipated in . These results suggest that SAPS-related strong westward ion drift might have induced the enhancement of LSSTID westward propagation components and may have even excited MSTIDs.…”
Section: Concurrent Mstids and Lsstidsmentioning
confidence: 83%
See 3 more Smart Citations
“…TOI shown in the figure was observed off the magnetic pole, more close to the dusk cell when the IMF By became negative. Simulations by Guo et al (2018) have suggested that SAPS related thermospheric heating can possibly induce regional thermospheric and ionospheric disturbances taking the form of TIDs/AGWs as anticipated in . These results suggest that SAPS-related strong westward ion drift might have induced the enhancement of LSSTID westward propagation components and may have even excited MSTIDs.…”
Section: Concurrent Mstids and Lsstidsmentioning
confidence: 83%
“…A secondary westward drift subsequently moved into the radar's field of view slightly after 00 UT on 8 September. SAPS can cause strong frictional heating (e.g., to both neutrals and ions and therefore can change the neutral density and composition in nearby regions (Guo et al, 2018;Wang et al, 2012). TOI shown in the figure was observed off the magnetic pole, more close to the dusk cell when the IMF By became negative.…”
Section: Concurrent Mstids and Lsstidsmentioning
confidence: 93%
See 2 more Smart Citations
“…Particle precipitations during geo-effective events often initiate traveling ionospheric disturbances (TIDs). These TIDs have been observed in TEC observations (e.g., Hajkowicz, 1990;Pradipta et al, 2016) as well as GCM simulations, including GITM (Guo et al, 2018;Lin, Deng, Venkataramani, et al, 2018). These TIDs can travel away from the source region, such as the auroral zone.…”
Section: Correlations With the Precipitation Patternsmentioning
confidence: 74%